Cellular Antioxidant Potential and Cytotoxic Activities of Extracellular Polysaccharides Isolated from Lactobacillus graminis Strain KNUAS018 - Kiseok Han; Kumar Vishven Naveen; Xin Zhang; Anbazhagan Sathiyaseelan; Hye-Yong Kim (Polysaccharides)
In the present study, exopolysaccharides (EPS-1, EPS-2, and EPS-3) were extracted from Lactobacillus graminis, and their chemical compositions, bioactivities, and cytotoxicity were comprehensively studied. A higher yield was observed for EPS-1 and EPS-2 with 14.38% and 9.24%, respectively. The chemical composition in the samples was studied using FT-IR analysis. The EPS-1 (1 mg/mL) showed higher antioxidant activities with 34.5 ± 6.6% and 93.6 ± 2.3% of DPPH and ABTS radical scavenging, respectively. In the cellular antioxidant assay, the EPS-1 protected oxidative stress-mediated cellular damage in AAPH-treated NIH3T3 cells. In addition, EPS-1 (0.25 mg/mL) treatment augmented the viability of AAPH-stressed RAW264.7 cells (~80%) than AAPH-treated cells (~50%) by reducing the ROS level and associated oxidative damage. Toxicity studies indicated that EPS-1 (1 mg/mL) did not induce notable cytotoxic effects in NIH3T3 cells, RAW264.7 cells, and erythrocytes. Altogether, the findings of this research suggest that L. graminis could be a source of biocompatible polysaccharides with antioxidant properties.